SCLE-LP overlap syndrome - C Shanmuga Sekar; Reena Rai; N Karthika; A Laila (Wolters Kluwer Medknow Publications, 2011)
A 35-year-old female presented with scaly annular and pigmented lesions all over the body of 2 years duration. Her clinical features, histopathology, immunofluorescence findings and positive ANA and anti-Ro antibodies were suggestive of subacute cutaneous lupus erythematosus-lichen planus. We report this case because of its clinical rarity.